Philosophy of God in The View of Philosophers - Zaprulkhan, Zaprulkhan (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2019)
In every episode of human history, every human being must need God. There is no one who is not godless, even though they worship God according to their respective perceptions of God himself. According to historians, human devotion to God, the Creator is something that is both essential and existential needs of every human being. This fact can be seen also in the historical-sociological intellectual exploration conducted by Karen Armstrong about the search for humanity against God. From classical times to modern times, in Armstrong's search it turns out that every human being always constructs the concept of God. It is done by theologians, philosophers, Sufis, or reformers. Therefore, this article will explore the existence of God in the perspectives of philosophers which includes ontological arguments, cosmological arguments, teleological arguments, moral arguments, and arguments of religious experience.